Association between periodontal disease and Alzheimer's disease: umbrella review - Arbildo-Vega, Heber Isac; Cruzado-Oliva, Fredy Hugo; Coronel-Zubiate, Franz Tito; Aguirre-Ipenza, Rubén; Meza-Málaga, Joan Manuel; Luján-Valencia, Sara Antonieta; Luján-Urviola, Eduardo; Echevarria-Goche, Adriana; Farje-Gallardo, Carlos Alberto; Castillo-Cornock, Tania Belú; Serquen-Olano, Katherine; Padilla-Cáceres, Tania; et al. (Frontiers in Dental Medicine, 2025)
BackgroundAlzheimer's disease (AD) and periodontal disease (PD) are both chronic conditions with rising global prevalence. Emerging research suggests a possible link between PD-induced systemic inflammation and neurodegeneration observed in AD.ObjectiveEmploy an umbrella review to look into the association between periodontal disease and Alzheimer's disease.Materials and methodsA comprehensive search was conducted until March 2025 across various electronic databases, including: PubMed, Cochrane Library, Scopus, SciELO, Web of Science, Google Scholar, ProQuest, and OpenGrey, and Dissertations and Theses. There were no time or language restrictions on the inclusion of systematic reviews (SR), with or without meta-analysis, as long as they looked at primary research that connected PD and AD. The following were excluded: preclinical and fundamental research, summaries, comments, case reports, protocols, personal opinions, letters, posters, literary or narrative reviews, fast reviews, intervention studies, and observational studies. The quality and general confidence of the included studies were evaluated using the AMSTAR-2 technique.ResultsA total of 358 items were found following the first search. 16 articles were left for additional review after the selection criteria were applied. With odds ratios (OR) and risk ratios (RR) ranging from 1.67 to 2.17 and 1.11 to 2.26, respectively, 14 studies showed a correlation between PD and AD.ConclusionsDrawing from the findings and conclusions of the SR demonstrating a high overall confidence, it's established that PD and tooth loss exhibit an association with AD.Systematic Review RegistrationRegistered in the Open Science Framework (OSF): DOI 10.17605/OSF.IO/GS367.